Exploration of the effect of blue light on microRNAs involved in the accumulation of functional metabolites of longan embryonic calli through RNA‐sequencing. (7th November 2018) - Li, Hansheng; Chen, Xiaohui; Wang, Yun; Yao, Deheng; Lin, Yuling; Lai, Zhongxiong
Abstract: BACKGROUND: The regulation of functional metabolites under light by structural genes and regulatory genes is understood but the roles of microRNAs in this pathway have rarely been reported and their regulation network is not yet clear. RESULTS: Blue light was most conducive to promoting the synthesis of some functional metabolites in longan embryonic callus (ECs). In this study, we sequenced three small RNA libraries of constructed longan ECs under different light qualities (dark, blue, and white). A total of 29 and 22 miRNAs were differentially expressed in the dark versus blue (DB) and dark versus white (DW) combinations, respectively. According to Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, most of the differentially expressed miRNA target genes were involved in plant hormone signal transduction, mitogen‐activated protein kinase (MAPK) signaling, biosynthesis of unsaturated fatty acids, and so on. Cytoscape analysis of the target genes of miRNAs indicated that miR396b‐5p and miR5139 had the most target genes in DB. Moreover, this study also found that miR171f_3 targeted DELLA, miR390e targeted BRI1, miR396b‐5p targeted EBF1/2 and EIN3 ; these miRNAs participated in the blue light signaling network through their target genes and regulated the accumulation of longan functional metabolites. CONCLUSIONS: The results of the study revealed that the expressions of phase‐specific miRNAs vary with the change of functional metabolites in longan ECs. This study provides new insights into the molecular mechanisms that allow light to influence plant metabolism. © 2018 Society of Chemical Industry